Творчество Марины Цветаевой в контексте гендерных исследований - Hrynyk, Agnieszka (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2012)
This article is an attempt to look at Marina Tsvetaeva’s literary output in the context of gender studies. The following aspects are briefly discussed: a woman as a writer, a womanartist defending her right to create, a woman telling/writing her story, gender performance, contravention of the gender role, and the apocryphal writing strategy. The basic material for the text are: On a Red Steed (1921), The Tsar-Maiden (1922), A Hero of Labour (1925).
Marina Tsvetaeva’s oeuvre in the context of gender studies
Twórczość Mariny Cwietajewej w kontekście gender studies